Mitos sobre a origem do ser humano em livros didáticos de História: a escola e a transmissão do conhecimento - Torresan, Carla (Universidade do Vale do Rio dos Sinos, 2018)
The research aims to analyze how the myths about the origin of the human being are present in textbooks of the 6th year of elementary school and that tensions are produced between the interests of religious groups related to these myths and the role of the school in the transmission of knowledge. The theoretical contributions that support it are found mainly in the contributions of Inés Dussel and Walter Kohan on the role of school, from the debate generated with the ideas of Jan Masschelein and Marteen Simons. The research material consists of: a) documents, which deal directly or indirectly with the origin of the human being, such as law projects, laws and decrees on religious teaching, and in some specific cases, on the teaching of creationism in schools; b) journalistic materials and interviews that deal with this subject and pedagogical experiences in public and private schools, involving the teaching of creationism; c) thirteen history books for teachers referring to the 6th year of elementary education, which are part of the National Textbook Program (PNLD) of 2017. The discussion of this material made it possible to problematize the school function in the transmission of knowledge, evidencing the strong performance of the religious bench of the Brazilian congress, nowadays, in the political field. This group, in an organized way, has created tensions in the school institution, in an attempt to change the school curriculum, to serve its interests. The analysis of texts, images, exercises and guidelines for teachers shows that the books examined privilege contents related to evolutionism, which is considered as science, differing from other explanations, which are identified as myths. Creationism is approached in a secondary way and little (or no) emphasis is given to other myths about the origin of the human being. Authors who approach other myths usually present them as curiosities, or as suggestions, to be worked on by teachers, demonstrating an encouragement to the clash between science and religion. The analysis of the research material allowed the identification of an attitude of resistance: the school seeks to resist the external pressures that act mainly through religious movements organized in the political field, aiming to introduce religious contents among those to be transmitted by it, and this resistance is expressed in textbooks.
Keywords: Evolucionismo; Criacionismo; Livros didáticos de História; Evolucionism; Creationism; History textbooks; ACCNPQ::Ciências Humanas::Educação